Effect of Psychological Conditioning Supported with Technology on Some Psychological Skills Tennis Players and Level of Performance for Table - Mervat Ahed Deeb; Hashem Adnan Kilani (Sultan Qaboos University, 2011)
The purpose of the study was to detect the effect of a psychological program supported by Macromedia Flash technology on some of psychological conditioning skills and the level of skills performance for table tennis players. Seven subjects comprised of 5 male and 2 female players from the Jordan national team with age ranges 12-15 year of old were intentionally selected. Measurement of muscle relaxation, mental imagery, state of competition anxiety, self talk, and colored readiness concentration (in-house built) for table tennis players. Skill performance during the competition was also assessed using special forms. Experiment design involved one group with pre and post hoc test after 12 weeks of the program application, 4 sessions per week in a simulated competition circumstances. Results of none parametric statistics (Welcoxon) revealed that there was a significant effect of the program at post hoc test for all skills variables. It is imperative to provide an early psychological conditioning program for table tennis juniors' players with practice sessions as it is important part of training regimen. In addition, it was suggested to use the Macromedia Flash technology for simulation enhancement of the real competition.